Network-Legacy Airline Business Model Developments in Post-COVID European Market - Hoszman, Adam; Zagrajek, Paweł (Journal of Management and Financial Sciences, 2025)
The deregulation of passenger air transport was the first major trigger of changes in airline business models. For more than two decades now the hybridization of the two major business models in aviation (network legacy airlines and low-cost carriers) has been observed but COVID-19 pandemic seems to have a strong catalytic effect in the ongoing process. The paper focuses on the developments of airline business models in the wake of the turbulence induced by the COVID-19 pandemic. The focus is on identifying market shifts that happened since 2020 that led to airlines seeking new opportunities to gain competitive advantage. Moreover, the authors aim at identifying how network-legacy carriers adjust their business models to catch up with their low-cost counterparts in terms of traffic recovery and growth. Following the COVID-19 pandemic network-legacy carriers (NLCs) were disadvantaged compared to low-cost carriers (LCCs). In response, NLCs further hybridized their business models, including targeting leisure and VFR markets to a larger extent. However, this strategy is not fully aligned with operational aspects of NLCs’ business model. As a result, this shift may be temporary.